2021
DOI: 10.1016/j.metabol.2020.154440
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat is associated to the severity of COVID-19

Abstract: Background: Excess visceral fat (VF) or high body mass index (BMI) is risk factors for severe COVID-19. The receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is expressed at higher levels in the VF than in the subcutaneous fat (SCF) of obese patients. Aim: To show that visceral fat accumulation better predicts severity of COVID-19 outcome compared to either SCF amounts or BMI. Methods: We selected patients with symptomatic COVID-19 and a computed tomography (CT) scan. Severe COVID-19 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
2
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 31 publications
(30 reference statements)
3
126
2
6
Order By: Relevance
“…Obese patients are at increased risk for complicated COVID-19 and related mortality. Moreover, altered body composition with increased visceral adiposity may negatively impact prognosis in subjects with COVID-19 [ 7 , 27 ].…”
Section: Main Endocrine Manifestations Of Covid-19 and Their Relevance To Pituitary Conditionsmentioning
confidence: 99%
“…Obese patients are at increased risk for complicated COVID-19 and related mortality. Moreover, altered body composition with increased visceral adiposity may negatively impact prognosis in subjects with COVID-19 [ 7 , 27 ].…”
Section: Main Endocrine Manifestations Of Covid-19 and Their Relevance To Pituitary Conditionsmentioning
confidence: 99%
“…The angiotensin-converting enzyme (ACE) 2 is the receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). An exploratory analysis found that ACE 2 mRNA expression in visceral fat (VF) positively correlated with BMI, and the engagement of SARS-CoV-2 on ACE 2 in the VF would impair the enzymatic activity of ACE 2 and enhance the production of inflammatory cytokines and their release into the systemic circulation ( 13 ). Therefore, we postulated the presence of MAFLD might exacerbate the virus-induced cytokine ‘storm’ associated with COVID-19, possibly through the hepatic release of multiple pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have shown that increased VAT deposition has a greater predictive value for adverse COVID-19 outcomes compared to BMI. This depot-specific adipose tissue dysfunction may be particularly relevant in younger cases 1821 . These results are consistent with previous findings in this population and further contribute to the characterization of the mechanisms underlying the risk attributable to aging and obesity in severe COVID-19 25–28 .…”
Section: Discussionmentioning
confidence: 99%